PENGARUH INTENSITAS MENGAKSES INSTAGRAM @BEAUTYJOURNAL TERHADAP PEMENUHAN KEBUTUHAN INFORMASI FOLLOWERS MENGENAI KECANTIKAN - Claritta Novelin, (2020)
Instagram as one of the social media with the most users makes it easy for users to share information through photos and videos. @beautyjournal is one of the online beauty media that uses the Instagram platform as a medium for disseminating information about beauty. The development of social media and online platforms that can be used by the public to exchange information and opinions makes the level of public knowledge of the world of beauty even increasing. The purpose of this study was to determine how much influence the intensity of accessing Instagram @beautyjournal on meeting the needs of followers' information about beauty. The theory used in this research is the theory of the use and fulfillment of satisfaction. This type of research is explanatory with survey methods. The population in this study Instagram followers @beautyjournal with a sample of 100 people using simple random sampling technique. The results of this study indicate that there is a significant influence and contribution between the intensity variable accessing Instagram @beautyjournal to the variable meeting information needs, with an effect value of 63.6%. Hypothesis test results also indicate H1 is accepted and H0 is rejected, which means that the higher the intensity of accessing Instagram @beautyjournal, the more fulfilling the needs of followers about beauty information.